Allay: Terminal year end report - Cruz, Jesus Alfonso C. (Animo Repository, 2022)
Allay is a corporation that is established and managed by the following individuals: Jesus Alfonso C. Cruz as the Chief Executive Officer, Grace Mariel M. Isais as the Chief Operating Officer, and Georliana Anne K. Reblando as the Chief Marketing Officer. Allay is created in order to introduce a more environment-friendly option for the fashion industry. It will be introducing fashion pieces made out of materials that have a low impact on the environment while at the same time, ensuring that their affiliations with other organizations uphold the rights of their respective laborers. The founders have decided to formulate this business venture as they were able to identify an opportunity in the fashion industry because global findings continue to indicate that consumers are slowly considering a product’s environment-friendly or sustainability aspects when patronizing a brand. The concept of fast fashion revolves around the mass production of clothing pieces sold at a cheap rate in order to gain profit as high and as fast as possible without consideration of its negative environmental and labor impacts. With this, the business’ vision and mission center on promoting responsible consumerism in order to constantly uphold the importance of environmental and human life. Included in the primary objectives of Allay is to attain brand popularity by 2030. The business is aiming for Millennials and Generation Z, both male and female individuals as their primary target market. The business aims to be one of the notable brands in the local fashion industry that are able to offer a more environmentally-friendly fashion option.